2016
DOI: 10.3109/14767058.2015.1126820
|View full text |Cite
|
Sign up to set email alerts
|

ST-analysis in electronic foetal monitoring is cost-effective from both the maternal and neonatal perspective

Abstract: Our study suggests that STAN, when compared to EFM alone, can be a cost-effective strategy from both a maternal and neonatal perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This concurs with comparable European research. An analysis (20) based on Individual Patient Data Metaanalysis (IPDMA) (21) incorporated data from three European trials of STan monitoring (12,987 mother/baby dyads). There was consistent reduction in neonatal metabolic acidosis.…”
Section: Main Findingsmentioning
confidence: 99%
“…This concurs with comparable European research. An analysis (20) based on Individual Patient Data Metaanalysis (IPDMA) (21) incorporated data from three European trials of STan monitoring (12,987 mother/baby dyads). There was consistent reduction in neonatal metabolic acidosis.…”
Section: Main Findingsmentioning
confidence: 99%
“…Despite the controversies in RCTs, many European obstetric units are now using ST analysis in clinical practice and some have published observational studies that have demonstrated a reduction in adverse perinatal outcomes. [40][41][42][43][44][45][46][47][48] Implementation of a new methodology typically requires that clinical users change their practice patterns in accordance with a set of new guidelines. However, prior to a methodology's becoming common practice, there is often a so-called learning curve, or a period of time during which experience is gathered and proficiency is attained.…”
Section: Introductionmentioning
confidence: 99%